Peran Guru Pendidikan Agama Islam Dalam Membentuk Ketahanan Moral Peserta Didik Terhadap Tantangan Sosial Era Digital di Pondok Pesantren Ulul Albab - Muhammad Rizki Maulana; Ruslan; M. Ra'di Al Ansyari (Universitas Majalengka, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in guiding students in facing adolescent social challenges at the Ulul Albab Islamic boarding school. This research uses a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation involving the head of the boarding school, PAI teachers, and students. Data were analyzed to identify patterns of social challenges and educational responses within the pesantren environment. The findings show that the main social challenges faced by students include the influence of social media, low self-control, problematic peer interaction patterns, and declining communication ethics. The results indicate that PAI teachers play a crucial role as mentors, motivators, supervisors, and role models in shaping students’ behavior. Character building is implemented through habituation of congregational worship, moral education, personal approaches, and consistent discipline in daily life at the boarding school. These efforts contribute positively to students’ character development, including improved discipline, responsibility, independence, and better control over social media use. However, the mentoring process still faces several obstacles, such as external environmental influences, uncontrolled gadget usage, and differences in student characteristics. The implications of this study suggest the need to strengthen structured mentoring systems, improve digital literacy and control policies, and reinforce pesantren-based character education to enhance students’ moral resilience in the digital era, while also recommending further research on broader contexts and additional variables. Additional materials in this study include interview guidelines, observation sheets, documentation records, and limited supporting tables, with a small number of references used to support the analysis.